2014
DOI: 10.11604/pamj.2014.18.308.4466
|View full text |Cite
|
Sign up to set email alerts
|

Sauti Za Wananchi “voice of the people”: patient's satisfaction on the medical wards at a Kenyan Referral Hospital

Abstract: IntroductionPatient satisfaction is one indicator of healthcare quality. Few studies have examined the inpatient experiences in resource-scarce environments in sub-Saharan Africa.MethodsTo examine patient satisfaction on the public medical wards at a Kenyan referral hospital, we performed a cross-sectional survey focused on patients’ satisfaction with medical information and their relationship with staffing and hospital routine. Ratings of communication with providers, efforts to protect privacy, information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(23 reference statements)
0
2
1
Order By: Relevance
“…Results of this study suggest that most of the participants were not satisfied with the overall quality of hospital meals. This is in contrast to the findings of a study conducted in India, which reported that majority of the patients were satisfied with hospital food [25]. However, study conducted in Kenya found that majority of the respondents rated food services as average [25].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Results of this study suggest that most of the participants were not satisfied with the overall quality of hospital meals. This is in contrast to the findings of a study conducted in India, which reported that majority of the patients were satisfied with hospital food [25]. However, study conducted in Kenya found that majority of the respondents rated food services as average [25].…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to the findings of a study conducted in India, which reported that majority of the patients were satisfied with hospital food [25]. However, study conducted in Kenya found that majority of the respondents rated food services as average [25]. Other studies conducted in Saudi Arabia and Egypt have reported that more than half of patients interviewed were satisfied with hospital food [6,26].…”
Section: Discussionmentioning
confidence: 66%
“…[19][20][21] The present study reported in general treatment satisfaction was higher compared to other studies. 7,22,23 This difference in estimation could be due to difference in the study setting. The hilly areas are still not creep in by private health sector as compared to plains.…”
Section: Discussionmentioning
confidence: 97%